2020
DOI: 10.1080/02786826.2020.1834073
|View full text |Cite
|
Sign up to set email alerts
|

Challenge of mechanical and antimicrobial filters against infectious phages artificially agglomerated with inorganic dust with a known particle-size distribution

Abstract: Duchaine (2020): Challenge of mechanical and antimicrobial filters against infectious phages artificially agglomerated with inorganic dust with a known particle-size distribution, Aerosol Science and Technology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…More recent aerosolized virus studies use the ASHRAE Standard 52.2 test duct. 26,31 This establishes an important level of consistency for future research. The aerosolized virus studies that state an explicit interest in SARS-CoV-2 used the bacteriophage MS2, which has a smaller size than SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…More recent aerosolized virus studies use the ASHRAE Standard 52.2 test duct. 26,31 This establishes an important level of consistency for future research. The aerosolized virus studies that state an explicit interest in SARS-CoV-2 used the bacteriophage MS2, which has a smaller size than SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 84%
“…Five of seven aerosolized virus studies found that filtration was associated with virus removal using PRRSV, 30 equine arteritis virus (EAV), 30 bovine enterovirus (BEV), 30 human adenovirus, 29 and the bacteriophages T7 [27][28] and MS2. 31 One study found that increasing MERV rating was associated with decreasing virus concentration for bacteriophage T4 40 at different locations within an apartment unit, and another found that increasing MERV rating was associated with increasing viral filtration efficiency using bacteriophage MS2 26 in a test duct set-up (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A consensus on an acceptable standard for virus reduction due to UV treatment might be helpful. Experimental studies may benefit from using the ASHRAE Standard 52.2 test duct which has been used in recent filtration studies [61,62]. Simply seeing more studies recognize that UV radiation dose is dependent on the radiant flux, which is often not uniform, shows a positive trend.…”
Section: Implications For Practicementioning
confidence: 99%
“…Experimental studies may benefit from using the ASHRAE Standard 52.2 test duct which has been used in recent filtration studies. [67][68] Simply seeing more studies recognize that UV radiation dose is dependent on the radiant flux, which is often not uniform, shows a positive trend. For ducted systems, flow that is well-mixed and close to uniform in velocity profile is helpful in evenly dosing aerosols with UV.…”
Section: Implications For Practicementioning
confidence: 99%